Advance in diagnosis and treatment of hepatopulmonary syndrome - Kai ZHAO; De-An TIAN (Yixue xinzhi zazhi)
Hepatopulmonary syndrome (HPS) is a common pulmonary complication of advanced liver disease. The disturbance of pulmonary ventilation/blood perfusion due to intrapulmonary vascular dilatations on the basis of acute/chronic liver disease or portal hypertension leads to dyspnea and hypoxemia. The early diagnosis rate of HPS is low, and the treatment is limited, which seriously affects the survival rate and quality of life of patients. In this article, we summary pathogenesis, clinical manifestations, diagnosis and treatment progress of HPS, in order to improve the clinical understanding and diagnosis level of HPS.